How would you differentiate the following ?

y=(2x^2-1)(4x^3+x)

and

y= (x+5) / (3x^2 -6x)

Printable View

- Mar 26th 2009, 09:58 PMnoshHelp deriving please
How would you differentiate the following ?

y=(2x^2-1)(4x^3+x)

and

y= (x+5) / (3x^2 -6x) - Mar 26th 2009, 10:29 PMJhevon
Here, apply the product rule: for differentiable functions $\displaystyle f$ and $\displaystyle g$, we define the derivative of their product as follows:

$\displaystyle (f \cdot g)' = f' \cdot g + f \cdot g'$

now try it

Quote:

y= (x+5) / (3x^2 -6x)

$\displaystyle \left( \frac fg \right)' = \frac {f'g - fg'}{g^2}$

now try it